The Quality Characteristics of Porang Flour Processed By Soaning, Flouring, Sifting, and Blowing Treatment - Ritzada, I Putu Dharma Putra; Rahayoe, Sri; Amanah, Hanim Zuhrotul (agriTECH, 2025)
Porang (Amorphophallus oncophyllus) is a raw material for glucomannan flour, which is widely used as a thickener in the food industry. However, the high oxalates in its flour can pose health risks when consumed in excess. Therefore, this study aimed to analyze the quality characteristics of porang flour processed through grinding with a hammer and disk mill, followed by polishing, sieving, and air blowing using a cyclone separator. The primary processing stages include the use of hammer and disk mills, a polishing machine, a Tyler sieving machine, as well as a cyclone separator equipped with a blower. The results showed that the quality of porang flour subjected to two polishing treatments produced a specific gravity of 0.559 g/cm 3 . Furthermore, the optimal processing method included hammer milling with a Sanindo  polished cycles. This led to the production of porang flour with the lowest calcium oxalate content (0.22%), high glucomannan concentration (31.56%), and high viscosity (14666.7 mPas).